2011
DOI: 10.1177/1352458511426815
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric multiple sclerosis: examining utility of the McDonald 2010 criteria

Abstract: The new McDonald 2010 criteria have been recommended in paediatric multiple sclerosis (PMS). We aimed to assess the utility of McDonald 2010 criteria in comparison with 2007 International Paediatric Multiple Sclerosis Study Group (IPMSSG)-recommended criteria for PMS diagnosis. Retrospective analysis of 38 PMS cases from three UK demyelination clinics was conducted. Dissemination in space (DIS) and time (DIT) for both McDonald and IPMSSG criteria were noted on initial and follow-up magnetic resonance imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…4447 Findings from all studies showed increased sensitivity of the 2010 criteria and indicated that use of the 2010 criteria led to an early diagnosis of multiple sclerosis. In a study of 212 paediatric patients with an acquired demyelinating syndrome, 47 followed prospectively for longer than 2 years with serial clinical and MRI assessments, the sensitivity of the 2010 criteria applied at baseline was 100%, the specificity 86%, the positive predictive value 59%, and the negative predictive value 100% for a subsequent diagnosis of multiple sclerosis.…”
Section: Multiple Sclerosis In Childrenmentioning
confidence: 99%
“…4447 Findings from all studies showed increased sensitivity of the 2010 criteria and indicated that use of the 2010 criteria led to an early diagnosis of multiple sclerosis. In a study of 212 paediatric patients with an acquired demyelinating syndrome, 47 followed prospectively for longer than 2 years with serial clinical and MRI assessments, the sensitivity of the 2010 criteria applied at baseline was 100%, the specificity 86%, the positive predictive value 59%, and the negative predictive value 100% for a subsequent diagnosis of multiple sclerosis.…”
Section: Multiple Sclerosis In Childrenmentioning
confidence: 99%
“…This revision to the McDonald criteria enables MS to be diagnosed even earlier in the disease course than does the previous 2005 version, as long as the criteria for dissemination in space are also fulfilled. The 2010 criteria are still being validated but initial reports support their utility (Gomez-Moreno et al, 2012;Sedani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The 2012 IPMSSG criteria (but not the Mc Donald 2010 criteria) required an age of 12 years or older for applying DIS and DIT criteria to diagnose MS at the time of the initial CIS. 1 However, subsequent studies [3][4][5][6] found that MS diagnostic criteria at CIS are applicable in younger children, provided that clinicians are aware that 2010 McDonald criteria have a lower positive predictive power and a higher false-positive rate.…”
Section: Evaluations Of 2012 Ipmssg and 2010 Mcdonald Criteria To Diamentioning
confidence: 99%
“…Five reports evaluated the accuracy of the 2010 McDonald criteria to diagnose MS in children, with similar results despite methodologic differences. [3][4][5][6][7] At time of first CIS, after application of the 2010 McDonald criteria to the initial brain MRI, the diagnosis of MS was met in 53%-63% of the children who subsequently developed a clinical relapse. DIT was less frequently present at initial brain MRI than DIS, which was observed in more than 80% of children.…”
Section: Evaluations Of 2012 Ipmssg and 2010 Mcdonald Criteria To Diamentioning
confidence: 99%
See 1 more Smart Citation